NIVELES SÉRICOS REFERENCIALES DE BILIRRUBINA, ALT, AST, GGT, PROTEÍNA Y ALBÚMINA EN Aotus nancymae - Ampuero G., Bruno (2002)
The objective of this work was to establish reference serum values for bilirrubin (total, direct and indirect), alanine amino transferase (ALT), aspartate amino transferase (AST), gamma glutamil transferase (GGT), total protein and albumin in healthy Aotus nancymae primate kept under captivity in the Amazon region of Peru. lt was used 30 animals (15 males and 15 females ), aged 7 months to 2 years, and raised at the Center ofReproduction and Conservation of Primates, IVITA, San Marcos University, located in !quitos, Loreto. The animals were trapped with nets, weighed and anesthesyzed for blood collection. Serum values were: Total bilirrubin: 0.76 ± 0.06 mg/dl; direct bilirrubin: 0.25 ± 0.03 mg/dl; indirect bilirrubin: 0.52 ± 0.06 mg/dl; ALT: 30.65 + 5.5 Ul/L; AST: 36.9 ± 5.69 Ul/L; GGT: 23.73 ± 2.56 Ul/L; total protein: 7 .53 ± 0.12 g/dl; and albumin: 3.83 ± 0.12 g/dl. It was concluded that serum values were similar to other results reported in the literature.